Investigative ethics ethics for police detectives and criminal investigators - Miller, Seumas (Wiley Blackwell, 2014)
"Investigative Ethics: Ethics for Police Detectives and Criminal Investigators presents applied philosophical analyses of the ethical issues that arise for police detectives and other investigators in contemporary society. Explores ethical issues relating to investigative independence, rights of victims and suspects, use of informants, entrapment, privacy and surveillance, undercover operations, deception, and suspect interviewing Represents the first monograph providing a detailed consideration of ethical issues in police investigations Features authorship by an applied philosopher specializing in police ethics, and a former UK senior police officer Combined authorship ensures the text is anchored in actual police practice as well as providing high quality ethical analysis" -- Provided by publisher.